1997
DOI: 10.1086/310447
|View full text |Cite
|
Sign up to set email alerts
|

Time Variability Detected in the Gamma-Ray Emission of 3C 273 by OSSE

Abstract: We report results of a 3 week observation of the quasar 3C 273 with the Oriented Scintillation Spectrometer Experiment (OSSE) instrument on the Compton Gamma Ray Observatory (CGRO). During the observation between 1994 August 31 and September 20, 3C 273 exhibited variability on timescales as short as 3-4 days in the 0.05-0.15 MeV energy range. This is the shortest measured variability of 3C 273 in this energy range. The measured flux at 100 keV is 2.40 H 0.06 (ϫ10 Ϫ2 ph cm Ϫ2 s Ϫ1 MeV Ϫ1 ), which is the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Here we present observational evidence supporting our choice of high T X associated with the spectra of some well known AGNs in ellipticals. For example, observations of 3C 273 in the range 150-800 keV by OSSE (McNaron-Brown et al 1997), show a double slope frequency distribution, with ξ 1 = 0.62, ξ 2 = 0.9 +1.6 −0.6 , and a break energy of 300 ± 100 keV. These values correspond (with a break energy of 200 keV) to T X ≃ 9.3 × 10 8 K, T X ≃ 5 × 10 8 K, and T X ≃ 10 8 K, for ξ 2 = 0.4, ξ 2 = 0.9, ξ 2 = 2.5, respectively.…”
Section: The Central Bhmentioning
confidence: 99%
“…Here we present observational evidence supporting our choice of high T X associated with the spectra of some well known AGNs in ellipticals. For example, observations of 3C 273 in the range 150-800 keV by OSSE (McNaron-Brown et al 1997), show a double slope frequency distribution, with ξ 1 = 0.62, ξ 2 = 0.9 +1.6 −0.6 , and a break energy of 300 ± 100 keV. These values correspond (with a break energy of 200 keV) to T X ≃ 9.3 × 10 8 K, T X ≃ 5 × 10 8 K, and T X ≃ 10 8 K, for ξ 2 = 0.4, ξ 2 = 0.9, ξ 2 = 2.5, respectively.…”
Section: The Central Bhmentioning
confidence: 99%
“…The best measurement up to now has been made by SAX [3], which found that the X-ray spectrum of 3C 273 from 1 to 200 keV follows a power-law with an index 1.57± 0.01. OSSE measurements [4,6] do not reach this level of accuracy, but low-energy experiments, like EX-OSAT, GINGA, and ASCA, have shown that a small spectral variability exists [5,1]. Taking this spectral variability into account, it means that the BATSE flux is not necessarily representative of the total X-ray flux.…”
Section: Correlation Without Delaymentioning
confidence: 99%
“…Since the lower γ-ray emission is produced closer to the central engine, it is likely that the GeV emission, produced further along the jet, is delayed in respect to the MeV emission. This model can also simply explain the appearance of a bump in the blazar spectra at energies below ∼ 0.511 MeV (the case of 3 C273, McNaron-Brawn et al 1997), which can not be explained by the e ± annihilation in the jet model. The peak in the γ-ray power spectrum, predicted by our model, is only determined by the balance between energy gains and energy losses of electrons propagating inside the thick disk (see Fig.…”
Section: Resultsmentioning
confidence: 98%